2015
DOI: 10.1016/j.cobeha.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Primate models of interference control

Abstract: Interference control is the ability to protect ongoing cognitive processing from internal or environmental distraction. For an individual to achieve interference control appropriately, either a control mechanism to coordinate multiple processing streams, such as the central executive in working memory, a mechanism to flexibly allocate the cognitive resource with a limited capacity for performing each task, or both, are needed. Through the use of dual-task paradigms, animal studies have provided important infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…This result concluded that a rat can act a task to simultaneously time two different times without being influenced by dual‐task interference. It is known that there are some dual tasks which rats can achieve in other previous studies , and our study explains that STP task by rats is also a useful experimental system to investigate neural mechanism of dual task. Practically, the STP tasks can be performed in an operant box for small animals used in common neurophysiological experiment, and it can repeat over dozens trials in one session, so that it has been used for an experiment to record neural activity in an example .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This result concluded that a rat can act a task to simultaneously time two different times without being influenced by dual‐task interference. It is known that there are some dual tasks which rats can achieve in other previous studies , and our study explains that STP task by rats is also a useful experimental system to investigate neural mechanism of dual task. Practically, the STP tasks can be performed in an operant box for small animals used in common neurophysiological experiment, and it can repeat over dozens trials in one session, so that it has been used for an experiment to record neural activity in an example .…”
Section: Introductionmentioning
confidence: 77%
“…It has been considered to be impossible for animals to achieve dual task because tasks are complicated and continuous and high concentration is required . However, there are a few studies on ethology of dual task aimed at monkeys . These previous studies presented that monkeys can also realize dual task, while dual‐task interference was further observed as in the case of human beings.…”
Section: Introductionmentioning
confidence: 99%
“…In more complex tasks, calling for locations to be stored across successive trials, a few prior studies of prefrontal cortex have reported observations similar to ours. For example, in a dual-task comprised of two spatial delay tasks, when the interleaved task is terminated, the main-task codes that had been outside the focus of attention are reactivated prior to the behavioral response for the main task 7 , 24 . Similarly, Barbosa et al showed that in the standard MGS task, although information about the target location in a trial disappeared soon after the completion of that trial, it was silently maintained across ITI by spike synchrony selective to the previous stimulus 25 .…”
Section: Discussionmentioning
confidence: 99%